Synthesis and Enantiomer Separation of 5-(1-(3,5-Dinitrobenzoylamino)pent-4-enyl)acenaphthene - Xu, Chao; Luo, Wen-Feng; Li, Li-Jun; Yao, Shun; Song, Hang (Asian Journal of Chemistry, 2010)
A new racemic (±) 5-(1-(3,5-dinitrobenzoylamino)pent-4-enyl)acenaphthene was synthesized and successfully separated into enantiomers on chiral HPLC. The synthetic approach to the 5- (1-(3,5-dinitrobenzoylamino)pent-4-enyl)acenaphthene is via Friedel-Crafts acylation reaction to the acenaphthyl ring, α-H substituent reaction to the ketone, deoxidization reaction to the ketone and amidation reaction to the amidocyanogen. The chemical structure of this compound was characterized by FT-IR and 1H NMR.